2022
DOI: 10.3390/ijerph19063463
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effects of Long Time Physical Activity Calorie Equivalent Labeling on Purchase Intention for Unhealthy Food

Abstract: (1) Background: Obesity has become a global epidemic that arouse much attention from governments, companies and scholar. Physical activity calorie equivalent (PACE) labels are introduced as a more effective nudge invention on less-calorie ordering. However, the effects of PACE labels are controversial in previous literature, thus, the research objective is to explore the effects of different PACE labels and furtherly to explore the underlying psychological mechanism; (2) Methods: Across four scenario-based exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…The following are the two labels' precise specifications (Figure 3): The words "calorie label" and "PACE label" stand for "2850 kj per serving" and "jogging for 80 min is required to burn off the calories," respectively. The contrasting paradigms PACE and calorie labels refer to previous mature studies [17].…”
Section: Procedures and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following are the two labels' precise specifications (Figure 3): The words "calorie label" and "PACE label" stand for "2850 kj per serving" and "jogging for 80 min is required to burn off the calories," respectively. The contrasting paradigms PACE and calorie labels refer to previous mature studies [17].…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…In a study on alcoholic drinks, PACE labeling had a significantly negative influence on participants drinking intentions [16]. Huang et al (2022) found that unhealthy food with a long time PACE label has a more negative effect on consumers' purchase intention than a short time PACE label [17]. However, a study by Ellison et al (2015) pointed out that few studies examine the context in which food consumption takes place; the effect of labels should be put in context, which means involving other factors [18].…”
Section: Introductionmentioning
confidence: 99%